Objective and subjective memory ratings in cannabis-dependent adolescents - McClure, Erin A. (Am J Addict, 2015)
BACKGROUND AND OBJECTIVES: Cannabis is the most widely used illicit substance worldwide, with an estimated 160 million users. Among adolescents, rates of cannabis use are increasing, while the perception of detrimental effects of cannabis use is declining. Difficulty with memory is one of the most frequently noted cognitive deficits associated with cannabis use, but little data exists exploring how well users can identify their own memory deficits, if present. METHODS: The current secondary analysis sought to characterize objective verbal and visual memory performance via a neurocognitive battery in cannabis-dependent adolescents enrolled in a pharmacotherapeutic cannabis cessation clinical trial (N=112) and compare this to a single self-reported item assessing difficulties with memory loss. Exploratory analyses also assessed dose-dependent effects of cannabis on memory performance. RESULTS: A small portion of the study sample (10%) endorsed a “serious problem” with memory loss. Those participants reporting “no problem” or “serious problem” scored similarly on visual and verbal memory tasks on the neurocognitive battery. Exploratory analyses suggested a potential relationship between days of cannabis use, amount of cannabis used, and gender with memory performance. CONCLUSIONS AND SCIENTIFIC SIGNIFICANCE: This preliminary and exploratory analysis suggests that a sub-set of cannabis users may not accurately perceive difficulties with memory. Further work should test this hypothesis with the use of a control group, comprehensive self-reports of memory problems, and adult populations that may have more years of cannabis use and more severe cognitive deficits.